Seismicity near the slip maximum of the 1960 Mw 9.5 Valdivia earthquake (Chile): Plate interface lock and reactivation of the subducted Valdivia Fracture Zone - Dzierma, Yvonne (2012)
Understanding the processes behind subduction-related hazards is an important responsibility and major challenge for the Earth sciences. Few areas demonstrate this as clearly as south-central Chile, where some of the largest earthquakes in human history have occurred. We present the first observation of local seismicity in the Villarrica region (39-40S), based on a temporary local network of 55 stations installed from the Chilean coast into the Argentinian back-arc for one year. While consistent with the Chilean national catalog (SSN), our results allow us to observe smaller magnitudes with a completeness of about 2.0 and image the geometry of the Wadati-Benioff Zone from the Chile Trench down to 200 km. Offshore, a gap in interplate seismicity is observed in the region of the 1960 Valdivia earthquake slip. Above the interface, two offshore seismicity clusters possibly indicate ongoing stress relaxation. In the subducting Nazca Plate, we find a prominent seismicity cluster along the extrapolated trace of the oceanic Valdivia Fracture Zone (VFZ). The seismicity cluster is observed between 70 and 130 km depth and comprises mainly strike-slip events. It indicates weakening and reactivation of the major VFZ by dehydration of oceanic crust and mantle. Interpreting the subducted VFZ section as a localized reservoir of potential fluid release offers an explanation for the Villarrica volcanic complex that is located above the reactivated VFZ and shows the highest volcanic activity in South America. Crustal seismicity is observed near Puyehue volcano, which recently started to erupt (June 2011).